2023
DOI: 10.1042/ebc20220136
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte heterogeneity and interactions with local neural circuits

Abstract: Astrocytes are ubiquitous within the central nervous system (CNS). These cells possess many individual processes which extend out into the neuropil, where they interact with a variety of other cell types, including neurons at synapses. Astrocytes are now known to be active players in all aspects of the synaptic life cycle, including synapse formation and elimination, synapse maturation, maintenance of synaptic homeostasis and modulation of synaptic transmission. Traditionally, astrocytes have been studied as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 115 publications
(148 reference statements)
1
18
0
Order By: Relevance
“…This work also substantiates the earlier hypothesis that astrocytes might be the principal CNS targets of NA McCarthy, 1989, 1992;Stone and Ariano, 1989). In future studies, it will be interesting to determine if α1-NAR signaling through astrocytes has the same consequences for neuromodulation in brain regions other than V1, especially considering that astrocyte heterogeneity, both between and within CNS regions, has emerged as an important factor defining astrocyte functions (Bayraktar et al, 2020;Pestana et al, 2020;Holt, 2023). For instance, earlier work has shown astrocytes in different CNS regions respond to α1-NAR activation, albeit with [Ca 2+ ] transients of different kinetics (Batiuk et al, 2020;Pham et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…This work also substantiates the earlier hypothesis that astrocytes might be the principal CNS targets of NA McCarthy, 1989, 1992;Stone and Ariano, 1989). In future studies, it will be interesting to determine if α1-NAR signaling through astrocytes has the same consequences for neuromodulation in brain regions other than V1, especially considering that astrocyte heterogeneity, both between and within CNS regions, has emerged as an important factor defining astrocyte functions (Bayraktar et al, 2020;Pestana et al, 2020;Holt, 2023). For instance, earlier work has shown astrocytes in different CNS regions respond to α1-NAR activation, albeit with [Ca 2+ ] transients of different kinetics (Batiuk et al, 2020;Pham et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Astrocyte heterogeneity has been an emerging consensus in recent studies (reviewed by Holt, 2023). Molecular characterization that captures mRNA distributed in astrocyte processes, for example, across cortical layers, describes differences in degree, rather than kind (Farhy‐Tselnicker et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike peripheral metastases, the emergence of BM depends on a plethora of environmental cues such as the spatiotemporal availability of factors that are provided by cells of the TME, supporting or repressing tumor cell growth 2 . Moreover, single-cell RNA sequencing (scRNAseq) studies have confirmed regional heterogeneity of astrocytes 3 , oligodendrocytes 4 and microglia 5,6 in healthy human brains. Particularly, astrocytes and microglia adopt a reactive cell state 7,8 that accompanies secretion of pro- and anti-inflammatory factors under pathological conditions 9, 10 .…”
Section: Introductionmentioning
confidence: 95%